Penerimaan Masyarakat Dalam Pemberian Akses Kerja Bagi Mantan Narapidana (Studi Kasus Dikecamatan Simeulue Timur Kabupaten Simeulue, Provinsi Aceh) - Imam, Imam Aulia Abdi; Sabirin, Sabirin; Amalia, Wirda (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
Former prisoners, most people do not really care about their existence, and in interacting with the community, they are not very friendly, just as they are. The problem is that they are stigmatized as people who are belittled. This stigma is often attached to those who can be belittled, namely groups of individuals including civil servants (Social Norm Deviants), for example former prisoners and former drug users. The giving of this stigma is a form of using power. Currently, the problem of former prisoners is not limited to the acceptance of society towards them, but is also seen from the side of job acceptance. Several studies have stated that many of the recipients of work automatically exclude workers who have a criminal background or are former prisoners. This study uses a qualitative approach and data collection is carried out through observation, interviews, and literature reviews. The results of the study show that the community in East Simeulue District, Simeulue Regency, Aceh Province generally still accepts former prisoners in daily interactions, but in terms of providing access to work or work trust, there are still people who have suspicions and concerns. Obstacles faced by former prisoners in accessing employment include the continued negative stigma against former prisoners and internal obstacles in the form of a lack of self-confidence among former prisoners.